Synergistic Effects of Sulfated Polysaccharides from Mexican Seaweeds against Measles Virus. (22nd June 2016) - Morán-Santibañez, Karla; Cruz-Suárez, Lucia Elizabeth; Ricque-Marie, Denis; Robledo, Daniel; Freile-Pelegrín, Yolanda; Peña-Hernández, Mario A.; Rodríguez-Padilla, Cristina; Trejo-Avila, Laura M.
Abstract : Sulfated polysaccharides (SPs) extracted from five seaweed samples collected or cultivated in Mexico ( Macrocystis pyrifera, Eisenia arborea, Pelvetia compressa, Ulva intestinalis, and Solieria filiformis ) were tested in this study in order to evaluate their effect on measles virus in vitro . All polysaccharides showed antiviral activity (as measured by the reduction of syncytia formation) and low cytotoxicity (MTT assay) at inhibitory concentrations. SPs from Eisenia arborea and Solieria filiformis showed the highest antiviral activities (confirmed by qPCR) and were selected to determine their combined effect. Their synergistic effect was observed at low concentrations (0.0274 μ g/mL and 0.011 μ g/mL of E. arborea and S. filiformis SPs, resp.), which exhibited by far a higher inhibitory effect (96% syncytia reduction) in comparison to the individual SP effects (50% inhibition with 0.275 μ g/mL and 0.985 μ g/mL of E. arborea and S. filiformis, resp.). Time of addition experiments and viral penetration assays suggest that best activities of these SPs occur at different stages of infection. The synergistic effect would allow reducing the treatment dose and toxicity and minimizing or delaying the induction of antiviral resistance; sulfated polysaccharides of the tested seaweed species thus appear as promising candidates for the development of natural antiviral agents.